Perencanaan Sarana Dan Prasarana Pada Lembaga Pendidikan - Mardiah Astuti; Icha Suryana; Putri Dea Novita; Emiliya Emiliya; Lina Sari; Rani Oktapiani (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research aims to understand the planning of educational facilities and infrastructure needs. Knowing the required facilities and infrastructure needs will have a significant impact on the success of the learning process and can contribute appropriately to the achievement of educational goals. The research method used is a literature review method by collecting materials from various sources such as journals, articles, the internet, books, and other sources related to the planning of educational facilities and infrastructure needs. The results of the study show that the steps in planning facilities and infrastructure needs include needs analysis, cost analysis, and priority analysis. The purpose of planning these facilities and infrastructure needs is to ensure the provision of facilities and infrastructure that meet the needs of students and the needs of all staff in educational institutions. This includes various specifications of items, such as consumables, non-consumables, immovable items, and items related to learning activities.